Dust Creation in CNC Drilling of Wood Composites - Tomasz Rogoziński; Jacek Wilkowski; Jarosław Górski; Paweł Czarniak; Piotr Podziewski; Karol Szymanowski (BioResources, 2015)
This paper presents the particle-size distribution of dust created by the drilling of selected wood composites, which was carried out using a CNC machine. The particle-size distribution was studied through two methods. Two analyses were performed: the sieve analysis of samples from the whole mass of collected dust and the laser diffraction analysis of the finest fraction isolated by sieving. The results presented general information about the particle-size distribution of the dust, as well as detailed information on the content of the finest particles. This information revealed that the particles might pose a potential risk to the health of workers employed in the woodworking industry. This potential risk is due to the possibility of their dispersion in the atmosphere surrounding the workplace and their size, which allows them to be respirable. The relationship between the fineness of the dust and the type of wood composite was also tested. Most ultrafine particles are formed during the drilling of fibreboards and are especially produced in traditional wet technology.